Hubungan Komponen Perilaku terhadap Pengunaan Alat Pelindung Diri pada Pekerja Pengelasan di PT. Industri Kapal Indonesia (Persero) Makassar, Sulawesi Selatan: Relationship between the Behavioral Component and the Use of Personal Protective Equipment in Welding Workers at PT. Industri Kapal Indonesia, Makassar, South Sulawesi - Uswantun Hasanah; Krisdayanti Krisdayanti; Andi Alim; Verawati Verawati (LPPM STIKES Guna Bangsa Yogyakarta, 2023)
The behaviour of workers in using PPE is relatively low which is caused by minimal knowledge, attitudes that consider PPE trivial, and actions that lack discipline. As a result, the emergence of the risk of accident hazards in the workplace. The purpose of this study was to determine the relationship between knowledge, attitudes and actions of using PPE for workers at PT. Industri Kapal Indonesia (IKI) Makassar, Tallo District, Makassar City, South Sulawesi Province. The type of research used is analytic research with a total sample of 49 people. The results showed that there was a relationship between knowledge and PPE users (p=0.05), there was a relationship between attitude and use of PPE (p=0.01), and there was a relationship between action and use of PPE (p=0.03). Based on the research findings, it is concluded that there is a relationship between knowledge, attitudes and actions with the use of PPE for welding workers. It is suggested to workers to always behave properly by using PPE and not using PPE half measures. The contribution of this research is to provide information on managing disciplinary behaviour in the use of PPE so that workers can avoid accidents that result in permanent disability or death.